Studi Analisa Rawan Tanah Longsor Dengan Metode Analytical Hierarchy Process di Jalan Lintas Pagar Alam – Lahat Kecamatan Pulau Pinang, Kabupaten Lahat, Sumatera Selatan - Xanana Mahesa Conforty; Endang Wiwik Dyah Hastuti (Teknik Geologi, Fakultas Teknik, Universitas Sriwijaya, 2022)
Pulau Pinang Subdistrict is one of the disaster prone areas in the form of soil or rock movements or both simultaneously, which moves down the slope due to slope instability. The condition of the slopes along the Pagar Alam – Lahat causeway is a critical slope. This research using 5 factors that cause landslides, namely slope, soil type, rainfall, geological conditions and land use. The purpose of this research was to determine the main factors causing landslides on the Pagar Alam – Lahat causeway, Pulau Pinang District, Lahat Regency. The results of the research that the main factors causing landslides were soil type with a weight value of 0.33 and the slope of the slope with a weight value of 0.23. Soil type is the most influencing factor for landslides in Pulau Pinang District. The rating for this factor is the highest compared to other factors according to the rating scale between elements. Data processing was carried out using the analytical hierarchy process (AHP) method. The results of field observations obtained 4 landslide points with a translational type. The first location is in Cuba Village with a slope of 340, the second location is in Lubuk Sepang Village with a 400slope, the third and fourth locations are in Tanjung Mulak Village with 330 and 440 slopes, respectively. Landslide hazard analysis map obtained critical slopes with steepness > 25%.